Prove that

Question:

Prove that $(1-\mathrm{i})^{\mathrm{n}}\left(1-\frac{1}{\mathrm{i}}\right)^{\mathrm{n}}=2^{\mathrm{n}}$ for all values of $\mathrm{n} \mathrm{N}$

 

Solution:

L.H.S $=(1-\mathrm{i})^{n}\left(1-\frac{1}{i}\right)^{\mathrm{n}}$

$=(1-\mathrm{i})^{\mathrm{n}}\left(1-\mathrm{i}^{-4^{*} 1+3}\right)^{\mathrm{n}}$

$=(1-i)^{n}\left(1-i^{3}\right)^{n}$

Since, $i^{4 n+3}=-1$

$=(1-i)^{n}(1+i)^{n}$

Applying $a^{n} b^{n}=(a b)^{n}$

$=((1-i)(1+i))^{n}$

$=\left(1-\mathrm{i}^{2}\right)^{\mathrm{n}}$

$=2^{\mathrm{n}}$

L.H.S = R.H.S

 

 

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now